Two grid finite element discretization method for semi‐linear hyperbolic integro‐differential equations. Issue 5 (7th March 2019) - Chen, Luoping; Chen, Yanping; Huang, Yunqing
Abstract : In this paper, we will investigate a two grid finite element discretization method for the semi‐linear hyperbolic integro‐differential equations by piecewise continuous finite element method. In order to deal with the semi‐linearity of the model, we use the two grid technique and derive that once the coarse and fine mesh sizes H, h satisfy the relation h = H 2 for the two‐step two grid discretization method, the two grid method achieves the same convergence accuracy as the ordinary finite element method. Both theoretical analysis and numerical experiments are given to verify the results.